2021
DOI: 10.1007/s00415-021-10803-3
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of death from COVID-19 in multiple sclerosis: a pooled analysis of observational studies

Abstract: Objective To estimate whether the risk of death from COVID-19 in patients with multiple sclerosis (MS) exceeds that of the general population. Methods We conducted a pooled analysis of cohort studies on COVID-19 in patients with MS published until July 31, 2021. We calculated the pooled crude death rate (CDR) and estimated the indirectly-adjusted age-standardized lethality ratio (SLR) to assess the risk of death from COVID-19 in patients with MS as compared to general population. Results Out of 520 articles, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 33 publications
4
18
0
Order By: Relevance
“…The present study extends findings from our recently published pooled analysis of observational studies where we found a 24%-increased risk of death from COVID-19 in patients with MS by an indirect standardization method (using as reference the age-specific case-fatality rates of COVID-19 in general population obtained from the WHO website) [ 7 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The present study extends findings from our recently published pooled analysis of observational studies where we found a 24%-increased risk of death from COVID-19 in patients with MS by an indirect standardization method (using as reference the age-specific case-fatality rates of COVID-19 in general population obtained from the WHO website) [ 7 ].…”
Section: Discussionsupporting
confidence: 88%
“…The interplay between MS-related disability, DMT-induced alteration of immune homeostasis and the coronavirus disease-19 (COVID-19) may possibly result in a higher risk of morbidity and mortality in these patients [ 6 ]. Currently available data suggest an approximately 24%-increased risk of death from COVID-19 in patients with MS than in the general population [ 7 ], mainly attributed to comorbidities and disease burden (i.e. progressive disease course and worse disability level [ 8 , 9 ]), whereas DMTs do not seem to affect survival [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…National data from the same period indicate that 431700 COVID-19 cases occurred in the northern region of Portugal, with 5645 confirmed deaths translating in 1.3% mortality rate, which is lower compared to our cohort. ( Saúde, 30-11-2021 ) This finding is consistent with some studies that have found higher mortality in patients with neurological diseases with COVID-19, namely patients with MS and MG, than in the general population with COVID-19 ( Muppidi, Guptill, and Jacob, 2020 , Prosperini et al, 2022 ), but there are studies that have not found this association ( Richter, Faissner, and Bartig, 2021 , Barzegar, Mirmosayyeb, and Gajarzadeh, 2021 ) Using the Portuguese national guideline, 11% of patients were classified as having severe or critical disease, similar to some MS cohorts. ( Zakaria, Ponzano, and Schiavetti, October 2021 ) However, other studies report values of 21.0 25 and 23.7% ( Parrotta, Kister, and Charvet, 2020 ), which may reflect sample size differences and the criteria used to define severe/critical COVID-19.…”
Section: Discussionsupporting
confidence: 88%
“…1,2 Of particular concern, B-cell depleting anti-CD20 therapies have been associated with an increased risk of infections and decreased humoral immune responses to vaccinations. [1][2][3][4][5][6] Indeed, serum levels of SARS-CoV-2 immunoglobulin (Ig)G following SARS-CoV-2 vaccinations and infections are reduced in anti-CD20 treated pwMS. [7][8][9] Nevertheless, in addition to antibody levels, protection from infection, and especially from severe courses of coronavirus disease-19 (COVID- 19), may depend on neutralizing capacity and avidity of anti-SARS-CoV-2 antibodies as well as on induction of SARS-CoV-2 specific T cells.…”
Section: Introductionmentioning
confidence: 99%